m-Carborane as a Novel Core for Periphery-Decorated Macromolecules - Bennour, Ines (Molecules, 2020)
Closom-C(2)B(10)H(12) can perform as a novel core of globular periphery-decorated macromolecules. To do this, a new class of di and tetrabranched m-carborane derivatives has been synthesized by a judicious choice of the synthetic procedure, starting with 9,10-I(2)-1,7-closo-C(2)B(10)H(10). The 2a-NPA (sum of the natural charges of the two bonded atoms) value for a bond, which is defined as the sum of the NPA charges of the two bonded atoms, matches the order of electrophilic reaction at the different cluster bonds of the icosahedral o-and m- carboranes that lead to the formation of B-I bonds. As for m-carborane, most of the 2a-NPA values of B-H vertexes are positive, and their functionalization is more challenging. The synthesis and full characterization of dibranched 9,10-R(2)-1,7-closo-carborane (R = CH(2)CHCH(2), HO(CH(2))(3), Cl(CH(2))(3), TsO(CH(2))(3), C(6)H(5)COO(CH(2))(3), C(6)H(5)COO(CH(2))(3), N(3)(CH(2))(3), CH(3)CHCH, and C(6)H(5)C(2)N(3)(CH(2))(3)) compounds as well as the tetrabranched 9,10-R(2)-1,7-R(2)-closo-C(2)B(10)H(8) (R = CH(2)CHCH(2), HO(CH(2))(3)) are presented. The X-ray diffraction of 9,10-(HO(CH(2))(3))(2)-1,7-closo-C(2)B(10)H(10) and 9,10-(CH(3)CHCH)(2)-1,7-closo-C(2)B(10)H(10), as well as their Hirshfeld surface analysis and decomposed fingerprint plots, are described. These new reported tetrabranched m-carborane derivatives provide a sort of novel core for the synthesis of 3D radially grown periphery-decorated macromolecules that are different to the 2D radially grown core of the tetrabranched o-carborane framework.